Effects of Delay Discounting and Other Predictors on Smoking Relapse. (2019) - González-Roz, Alba; Secades-Villa, Roberto; Pericot-Valverde, Irene; Weidberg, Sara; Alonso-Pérez, Fernando
Abstract: Despite the substantial decrease in the prevalence of tobacco smoking and the availability of effective smoking cessation treatments, smoking relapse after formal treatments remains extremely high. Evidence regarding clinical predictors of relapse after quitting is essential to promote long-term abstinence among those who successfully quit. This study aimed to explore whether baseline delay discounting (DD) rates and other sociodemographic, psychological, and smoking-related variables predicted relapse to smoking at six-month follow-up. Participants were 188 adult smokers (mean age = 42.9, SD = 12.9; 64.4% females) who received one of three treatment conditions: 6-weeks of cognitive–behavioral treatment (CBT) alone; or combined with contingency management (CBT + CM); or combined with cue exposure treatment (CBT+CET). Smoking status was biochemically verified. Logistic regression was conducted to examine prospective predictors of smoking relapse at six months after an initial period of abstinence. Greater DD rates ( OR : 0.18; 95% CI [0.03, 0.93]), being younger ( OR : 0.96; 95% CI [0.94, 0.99]), high nicotine dependence ( OR : 1.34; 95% CI [1.13, 1.60]), and a higher number of previous quit attempts ( OR : 4.47; 95% CI [1.14, 17.44]) increased the likelihood of smoking relapse at six-month follow-up. Besides sociodemographic and smoking-related characteristics, greater DD predisposes successful quitters to relapse back to smoking. These results stress the relevance of incorporating specific treatment components for reducing impulsivity.